Teaching Technique Applied By English Teacher To Improve Students' Vocabulary At The First Year Of SMP Muhammadiyah 7 Eromoko Wonogiri In 2012/2013 Academic Year - Sari., Siwi Ardilla; , Drs. Djoko Srijono, M. Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research paper aims at (1) describing the teacher's technique in improving students' vocabulary at the first year, (2) identifying the problem faced by teacher in the process of teaching-learning vocabulary at the first year, (3) describing the problem solving used by teacher in teaching-learning vocabulary at the first year of SMP Muhammadiyah 7 Eromoko Wonogiri in 2012/2013 academic year. This is a descriptive research. The object of the study is focussed on the technique of English teacher applied in improving vocabulary in the first year of SMP Muhammadiyah 7 Eromoko Wonogiri in 2012/2013 academic year. The methods of collecting data are observation, interview and analyzing document. The data are taken from the result of event, informant, and document. The conclusion of this research shows that the technique of teachinglearning vocabulary consisting of memory and storage systems and contextual guesswork has a good result for development students' vocabulary. The students are not bored, but more enthusiastic to follow the teaching-learning process. The process of teaching-learning vocabulary consists of opening the class, explanation, consultation, practice, presentation, evaluation, and closing. The problem faced by the teacher in teaching vocabulary at the first grade students is the classroom management, different motivation of the students, and the different ability of each student in acquiring vocabulary. The problem solving applied by teacher in teaching vocabulary is by using group work to manage the number of the students that is overload, arranging the position of the student's seats in the class, giving advices, motivation, and using interesting media like picture and game to attract the student's attention in English teaching-learning process.